2011
DOI: 10.1016/j.juro.2011.02.059
|View full text |Cite
|
Sign up to set email alerts
|

Independent Validation of the 2010 American Joint Committee on Cancer TNM Classification for Renal Cell Carcinoma: Results From a Large, Single Institution Cohort

Abstract: The new 2010 classification remains a robust predictor of cancer specific survival compared to the 2002 classification by dividing pT2 lesions into pT2a and pT2b, reclassifying ipsilateral adrenal involvement as pT4, reclassifying renal vein involvement as pT3a and simplifying nodal involvement as pN0 vs pN1. However, the 2010 TNM classification showed only modest improvement in predictive ability compared to the 2002 classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 22 publications
2
102
1
Order By: Relevance
“…The prognostic value of the 2010 TNM classification has been validated in both single-and multiinstitutional studies [37]. However, the subclassification of T1 tumours using a cutoff of 4 cm might not be optimal with the widening indication for nephron-sparing surgery for localised RCC.…”
Section: Tnm Stage Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic value of the 2010 TNM classification has been validated in both single-and multiinstitutional studies [37]. However, the subclassification of T1 tumours using a cutoff of 4 cm might not be optimal with the widening indication for nephron-sparing surgery for localised RCC.…”
Section: Tnm Stage Classificationmentioning
confidence: 99%
“…In comparison to the 2009 version, there is no longer any distinction between N1 metastasis in a single regional lymph node and N2 metastases in more than one regional lymph node. Instead, N1 comprises metastasis in regional lymph node(s) [37].…”
Section: Tnm Stage Classificationmentioning
confidence: 99%
“…The improvements evidenced by this reclassification came about mainly as a consequence of the inclusion of adrenal invasion, a strong adverse prognostic factor, in the T4 disease category. In previous studies, both Novara et al 5 and Kim et al 11 showed that there was a significantly different survival rate between the T3a and T3b subgroups according to the revised 2010 staging system. Kaplan-Meier plots showed a significant difference in survival between the T3a and T3b subgroups (log-rank, P50.03), indicating that the 2010 TNM staging system could accurately distinguish survival between T3a and T3b tumours.…”
Section: Discussionmentioning
confidence: 94%
“…When compared with the 2002 TNM classification, novel 2010 TNM classification slightly improved prognostic accuracy (11,13). Ease of use, accumulated knowledge, and wide spread use of TNM primary staging systems maintain its contribution to other predictive models (14,15).…”
Section: Resultsmentioning
confidence: 99%